Relationship of Obesity on Self-esteem and Academic Performance Among Undergraduate Students - Haque, Mansoor ul; Siddiqui, Muhammad Ilyas; Akhtar, Parveen; Shaoowal, Aisha; Channar, Husan Bano; Akhtar, Tasleem (Indus Journal of Bioscience Research, 2024)
Introduction: Overweight is a major global health concern that has a wide-ranging impact on people's life, particularly physical health, psychological wellness, and academic achievement. Obesity can have a substantial impact on under graduates’ physical well-being, self-esteem, and their academic achievement. Material and Methods: A comparative cross-sectional research was carried out at Liaquat University of Medical & Health Science Jamshoro. Subjects of the study were Students of BS Nursing (Generic), Doctor of Pharmacy and Doctor of Physiotherapy, both males and females were included, and the sample size was 351. The Questionnaire was used as a data collecting tool consisting of three sections. Section One Demographic variables. Section 2 consists of Academic Performance Scale while Section 3 consists of Rosenberg Self-esteem Scale. Results: Data was analyzed by statistical package for social sciences version (SPSS) 23 Latest version. among351 undergraduate students. The mean age was 21.6 years, 34.8% females and 65.2% males. There was a significant association between self-esteem and BMI, with low self-esteem linked to higher BMI (p=0.016). Conclusion: Study revealed a significant association between BMI and academic performance, with students performing excellently more likely to have lower BMI and poorer academic performance association with higher BMI.